2005
DOI: 10.1111/j.1745-4530.2005.034.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Acrylamide Formation During Traditional and Vacuum Frying of Potato Chips

Abstract: Acrylamide is considered a carcinogen in animals and a possible carcinogen in humans. It has been found in starch‐rich foods cooked at high temperatures. Vacuum frying (10 Torr) was investigated as a possible alternative to reduce acrylamide formation in potato chips. The cultivar Atlantic was used to determine the kinetics of acrylamide formation during traditional and vacuum frying at different temperatures. There was a 94% decrease in acrylamide content when potatoes were fried to the same final moisture co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 18 publications
4
43
0
2
Order By: Relevance
“…Pedreschi et al [73] Troncoso and Pedreschi [97] VF divided into three periods: frying, pressurization and cooling Garayo and Moreira [34] Oil content VF sweet potato chips significantly lower than AF Da Silva and Moreira [21] VF apple slices reduce oil content compared with AF Mariscal and Bouchon [55] VF increased significantly oil content in potato chips Troncoso et al [98] VF produce more oil uptake in donut Tan and Mittal [92] VF gilthead sea bream fillets oil content lower than AF Andrés-Bello et al [6] VF may reduced the oil content of carrot chips by nearly 50% (db) Dueik et al [27] Color VF preserving the color of the apple slices compared with AF Mariscal and Bouchon [55] VF retained or accentuated the original color of sweet potato Da Silva and Moreira [21] VF produced L* values significantly higher than AF in potato chips Troncoso et al [98] Biocompounds VF preserve of 90% of trans a-carotene and 86% of trans p-carotene in carrot chips Dueik et al [27] Anthocyanin and total carotenoids significantly higher in Vf than AF potato chips Da Silva and Moreira [21] Texture VF produce a less compact texture in donut Tan and Mittal [92] Texture quality significantly ''better'' in VF potato chips Troncoso et al [98] Acrylamide Increase in acrylamide content less drastic in VF than AF Granda and Moreira [38] researches have been oriented toward fruits and vegetables, especially potatoes, and only few studies based on other foods are found [85,87].…”
Section: Water Lossmentioning
confidence: 96%
“…Pedreschi et al [73] Troncoso and Pedreschi [97] VF divided into three periods: frying, pressurization and cooling Garayo and Moreira [34] Oil content VF sweet potato chips significantly lower than AF Da Silva and Moreira [21] VF apple slices reduce oil content compared with AF Mariscal and Bouchon [55] VF increased significantly oil content in potato chips Troncoso et al [98] VF produce more oil uptake in donut Tan and Mittal [92] VF gilthead sea bream fillets oil content lower than AF Andrés-Bello et al [6] VF may reduced the oil content of carrot chips by nearly 50% (db) Dueik et al [27] Color VF preserving the color of the apple slices compared with AF Mariscal and Bouchon [55] VF retained or accentuated the original color of sweet potato Da Silva and Moreira [21] VF produced L* values significantly higher than AF in potato chips Troncoso et al [98] Biocompounds VF preserve of 90% of trans a-carotene and 86% of trans p-carotene in carrot chips Dueik et al [27] Anthocyanin and total carotenoids significantly higher in Vf than AF potato chips Da Silva and Moreira [21] Texture VF produce a less compact texture in donut Tan and Mittal [92] Texture quality significantly ''better'' in VF potato chips Troncoso et al [98] Acrylamide Increase in acrylamide content less drastic in VF than AF Granda and Moreira [38] researches have been oriented toward fruits and vegetables, especially potatoes, and only few studies based on other foods are found [85,87].…”
Section: Water Lossmentioning
confidence: 96%
“…Potato chips fried under vacuum absorbed more oil when the frying temperature was increased [10,11]. Additionally, most of the reports on VF focused on its effect as drying process, aiming at the quality of the dried products but neglecting the performance of the frying fats [11][12][13][14].…”
Section: Introductionmentioning
confidence: 98%
“…This variation can be as a result of the different composition and processing conditions in different brands and types of food samples since acrylamide formation is directly related to these factors. Differences in the raw material composition such as free asparagine and reducing sugar content, food product formulations, processing methods and parameters such as pH, water content, high temperature (more than 120°C) and time could be the sources for variation in acrylamide levels as reported by other researchers [7,8,[45][46][47][48][49][50][51][52][53][54][55][56][57]. Crackers with spices were the sub-group of crackers containing appreciably high levels of acrylamide with mean and the highest values of 1376 and 2666 mg/kg, respectively.…”
Section: Resultsmentioning
confidence: 96%